Nonlinear management programming for grid connected hybrid system combined to e-mobility facility. (22nd April 2021) - Tabaa, Mohamed; Chakir, Asmae; Moutaouakkil, Fouad; Medromi, Hicham; Alami, Karim
The integration of renewable energy sources is a very essential point in the strategic list that has to be met by the different countries' governments to combat the constraints of the 21st century that the increased electricity demand in the residential sector represents the front-line constraints. However, the problem of intermittency inevitably arises. As a result, an optimal energy management represents the most intelligent solution to smoothen the energy profile during cases of extreme renewable production or critical energy shortages. Furthermore, in the second row the transport sector with major consumption of energy in a given country is regarded. For this reason, in a sense, to reduce greenhouse gas emissions that threatens the environmental climate, the development of transportation electrification combined to households equipped with a grid connected PV-wind-battery hybrid system is investigated in this paper. In fact, to take advantage of the integration of renewable energy systems to residential sector as well as the notion of transport electrification, the two notions are combined for electric vehicles with renewable energy charging. Indeed, the energy management of the global hybrid architecture is proposed via a nonlinear programming algorithm and validated with MATLAB simulation.